Activation of TLR4-Mediated NFκB Signaling in Hemorrhagic Brain in Rats. (14th December 2009) - Teng, Weiyu; Wang, Lishu; Xue, Weishuang; Guan, Chao
Abstract : Inflammation and immunity play a crucial role in the pathogenesis of Intracerebral hemorrhage (ICH). Toll-like receptor 4- (TLR4-) mediated nuclear factor kappa-B (NFκ B) signaling plays critical roles in the activation and regulation of inflammatory responses in injured brain. However, the involvement of TLR4-mediated NFκ B signaling in the pathogenesis of ICH remains unknown. The present study was to evaluate the temporal profile of the expression of TLR4 and the activation of TLR4-mediated NFκ B signaling in brain tissues of Wistar rats after ICH. TLR4 mRNA and protein, the phosphorylation of inhibitors of kappa B (p-Iκ Bα ), and the activity of NFκ B were examined in hemorrhagic cerebral tissue by Rt-PCR, Western blots, immunohistochemistry staining, and EMSA. Compared with saline control, the TLR4 mRNA and protein significantly increased starting at 6 hours after ICH, peaked on the 3rd day after ICH, and then decreased but still maintained at a higher level on the 7th day after ICH (P < .05 ). The level of p-Iκ Bα and the activity of NFκ B also increased in the brain after ICH compared with saline control. The present study firstly suggests that TLR4-mediated NFκ B signaling participates in the pathogenesis of ICH, which may become a therapeutic target for ICH-induced brain damage.